Droga Hamburga w kierunku metropolii globalnej - Wartalska, Magdalena; Podgórniak-Krzykacz, Aldona (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The world's globalization process causes an increase in competition among cities in order gain the best local, national and international position. By taking many actions and organizational ventures in the process of winning miscellaneous advantages such as: winning over new investors; financial sources or localization of public institutions, the cities become independent organisms at the same time that the political, social and economic life develops. Hamburg is an example of such a city. The body of this article is a depiction of conditions and directions of developing Hamburg as well as changes made in its economy. Contemporary image of the city has shaped itself based on economic transformations that have been made in decades. Laba River and inland navigation, with the function as a port city played an important role and has made Hamburg wealthy. Up to this day, not only modern services and market but also industries are the main factors of Hamburg's growth. Nowadays, Hamburg is visualized as the city of great development perspectives, which has a good chance of becoming world metropolis in the near future. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 199-209